PTU-074 Optimising crohn's disease treatment based on the rutgeerts' score 12 months after ileo-colic resection improves clinical outcomes at 3 years compared to standard practice. (22nd June 2015) - Kailey, BS; Blaker, PA; Macken, L; Rajashekar, D; Harris, AW
Abstract : Introduction: Clinical relapse of Crohn's Disease (CD) occurs in 20–30% of patients at 1 year following intestinal resection, increasing by 10% per year without treatment. 1 Work by Rutgeerts' et al . 2 within a tertiary centre supports the practice of ileo-colonoscopy 12 months post-resection to assess endoluminal recurrence, however the validity of this practice is unclear in a general hospital setting. The European Crohn's and Colitis Organisation (ECCO) recommend the use of the Rutgeerts' score at 12 months following ileo-colic resection to guide treatment decisions. This is not supported by the current BSG guidelines. The aim of this study is to assess the utility of the 12-month Rutgeerts' score to improve clinical outcomes at 3 years following ileo-colic resection. Method: Prospective analysis of 50 patients with CD requiring ileo-colic resection and primary anastomosis in a District General Hospital (DGH) between 2005–2011. Thirty eight of fifty patients underwent endoscopic appraisal of the pre-anastomotic ileum by a single expert observer (AWH) 12 months following resection. Patients with high risk lesions (≥ i3) were offered a step-up in treatment. Patients with low risk-lesions (i0-i1) had their treatment stopped completely or continued on their current regimen. Clinical outcomes at 3 years were compared between these 38 patients and 12 of 50 patients who refused 12 month endoscopic appraisal and received standard care. Fisher's Exact Test was used to compare groups. Results: Thirty six of thirty eight patients whose treatment was guided by 12 month endoscopic appraisal remained in steroid and symptom-free remission at 3 years. In comparison 5 of 12 patients receiving standard care suffered recurrence. The difference in clinical outcomes at 3 years between groups was significant (P = 0.0059, OR 12.86 (95% CI 2.064–80.09); Fisher's Exact Test). There was trend towards higher Rutgeerts' scores (≥ i3, n = 2 0) being associated with a higher risk of disease relapse at 3 years as compared to low Rutgeerts' scores (i0-i1, n = 1 7) but this did not reach statistical significance (P = 0.0606, OR 10.00 (95% CI 0.993–100.7)). Conclusion: In comparison with standard practice, optimising treatment paradigms guided by the Rutgeerts' score 12 months following ileo-colic resection improves clinical outcomes at 3 years in DGH practice. Disclosure of interest: None Declared. References: Carter MJ, et al . Gut 2004;53 (Suppl V):v1-v16 Rutgeerts P, et al . Gastroenterology 1990;99(4):956–63